2022
DOI: 10.1177/21582440221096133
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Driving: A Comparison of Driving Performance Between Older and Younger Drivers in an On-Road Driving Test

Abstract: It is important to examine changes in driving performance and driver behavior with increasing age to improve road safety. The main purpose of this study was to explore if there were any differences in a group of young drivers ( n = 36, Mage = 32) and a group of elderly drivers ( n = 40, Mage = 72) on driving performance and driving skills on a number of driving tasks. An on-road driving test was conducted using a fixed 25-km route lasting approximately 30 minutes. Expert examiners assessed the participants’ dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Safety margin from the preceding vehicle was found to be positively correlated with older age and with female gender (for the latter, only in one scenario). Previous studies have shown that ageing affects driving [ 84 , 85 ], but also that driving performance is affected to a lower degree than expected and commonly assumed, because probably older drivers use compensatory actions [ 86 , 87 ]. It is known that driving skills decline with age, and it is a possibility that the longer safety distance maintained by older participants of our sample reflects a compensatory measure in accordance with the above studies [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Safety margin from the preceding vehicle was found to be positively correlated with older age and with female gender (for the latter, only in one scenario). Previous studies have shown that ageing affects driving [ 84 , 85 ], but also that driving performance is affected to a lower degree than expected and commonly assumed, because probably older drivers use compensatory actions [ 86 , 87 ]. It is known that driving skills decline with age, and it is a possibility that the longer safety distance maintained by older participants of our sample reflects a compensatory measure in accordance with the above studies [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ageing affects driving [ 84 , 85 ], but also that driving performance is affected to a lower degree than expected and commonly assumed, because probably older drivers use compensatory actions [ 86 , 87 ]. It is known that driving skills decline with age, and it is a possibility that the longer safety distance maintained by older participants of our sample reflects a compensatory measure in accordance with the above studies [ 86 , 87 ]. Finally, lateral position stability was found to decline with advancing age, in accordance with another study comparing older and younger drivers [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…As life expectancy increases and there are medical advances improving recovery from illness, there are more people requiring reassessment of their driving skill [1]. The driver safety issue in the elderly demographic has been reviewed at length in the literature with older age causing decline in cognition that impacts on driving performance, however far less than perceived in the wider community [2]. Driving has been linked with feelings of normality, a marker of recovery from disability or illness and is often considered critical to someone's own identity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Young adults are more likely to be involved in fatal MVCs than any other age group (National Center for Statistics and Analysis, 2021), potentially due to inexperience and still-developing frontal brain regions that may promote risky driving behaviors (Williams, 2003). Older adults similarly face elevated risk of MVC-related injury and death (Meuleners et al, 2006;Cicchino and Mccartt, 2014), due to age-and health-related declines in the psychomotor skill and cognitive domains that support safe driving (Leversen et al, 2013;Robertsen et al, 2022). Physicians and governments should aim to minimize the risk of MVCs for adults across the age span (Carr et al, 2006), which requires the identification of high-risk drivers and driving behaviors.…”
Section: Introductionmentioning
confidence: 99%